Encountering the Crucified God: the Soteriology of Sebastian Moore - Loewe, William P. (Horizons, 1982)
These reflections on Sebastian Moore's soteriology fall under four headings. By way of introduction and in order to establish a context, I commemorate an anniversary (I). There follows an effort to state in summary fashion what I understand Moore to be saying and what I understand him to be doing in what he says (II). A third section contains a suggestion concerning the ecumenical significance of Moore's work (III). The paper concludes with a number of critical observations and proposals for further work (IV).